Visceral Kaposi’s Sarcoma Presenting as Upper Gastrointestinal Bleeding - Naomi Hauser; Devon McKenzie; Xavier Fonseca; Jose Orsini (Case Reports in Gastrointestinal Medicine)
Since the advent of highly active antiretroviral therapy (HAART), the incidence of acquired immunodeficiency syndrome- (AIDS-) related Kaposi’s sarcoma (KS) has decreased dramatically. While cutaneous KS is the most common and well-known manifestation, knowledge of alternative sites such as the gastrointestinal (GI) tract is important. GI-KS is particularly dangerous because of its potential for serious complications including perforation, obstruction, or bleeding. We report a rare case of GI-KS presenting as upper GI bleeding in a human immunodeficiency virus- (HIV-) infected transgendered individual. Prompt diagnosis and early initiation of therapy are the cornerstones for management of this potentially severe disease.